Nord Stream and South Stream as innovative projects, their impact on the energy sector environment and policies of the European Union - Nikitina, Ludmiła (Rocznik Integracji Europejskiej, 2014)
Natural gas is an indispensable resource in many industries. Its share in the primary energy consumption is relatively high, both in the European Union and globally. Energy security is a priority for each country, making the diversification of suppliers, energy sources and the construction of energy transmission systems come first in its implementation of energy policy goals. The paper discusses the following issues: – the growing demand for gas in the European Union and its consumption forecasts. Energy security – diversification of gas suppliers and transmission systems. Innovative projects Severnyi Potok (Nord Stream) and Yuzhny Potok (South Stream). Political controversies and economic reality. The analysis of media rhetoric on this topic; – do Nord Stream and Yuzhny Potok (South Stream) pose a threat to the energy security of the European Union, or are they strategically important projects, ensuring the stable and secure supplies of natural gas to EU countries? Environmental protection and the Nord Stream and South Stream pipelines. Economic cooperation between European and Russian companies in the implementation of the above projects.